Technical use of intravascular ultrasound in chronic total occlusion percutaneous coronary interventions: insights from the Euro-CTO registry - Arioti, Manfredi; Moroni, Alice; Mashayekhi, Kambis; Werner, Gerald S.; Agostoni, Pierfrancesco; Gorgulu, Sevket; Ayoub, Mohamed; Avran, Alexandre; Kalay, Nihat; Goktekin, Omer; Ladwiniec, Andrew; Zaczkiewicz, Myron; et al. (Clinical research in cardiology, 2025)
Intravascular ultrasound (IVUS) plays a central role in complex percutaneous coronary interventions (PCI). While guidance for stenting and optimization is the most common reason for IVUS use, the technical application of IVUS for greater procedural efficiency is becoming increasingly important. The impact of IVUS has been only partially investigated in its technical aspect.
Gesehen am 20.11.2025